Development of an online research platform for use in a large-scale multicentre study. Issue 1 (11th February 2021) - Godden, A R; Micha, A; Pitches, C; Barry, P A; Krupa, K D C; Rusby, J E
Abstract: Background: Participation in research can be beneficial for patients and healthcare providers, but may prove demanding at patient, clinician and organizational levels. Patient representatives are supportive of online research to overcome these challenges. The aim of this pilot study was to develop an online recruitment platform and test its feasibility and acceptability while evaluating the accuracy of participant-reported data. Methods: The online research platform was developed in a 1-day 'hackathon' with a digital design company. Women who underwent implant-based breast reconstruction in 2011–2016 were invited by letter containing the web address (URL) of the study site and their unique study number. Once online, participants learned about the study, consented, entered data on demographics, treatment received and patient-reported outcome measures (BREAST-Q™), and booked an appointment for a single hospital visit for three-dimensional surface imaging (3D-SI). Real-time process evaluation was performed. The primary endpoint was recruitment rate. Results: The recruitment rate was 40 per cent. Of the 100 women, 50 logged on to the platform and 40 completed the process through to 3D-SI. The majority of discontinuations after logging on occurred between consenting and entering demographics (3 women, 6 per cent), and between completing the BREAST-Q and booking an appointment for 3D-SI using the online calendar (3 women, 6 per cent). All women completed the online BREAST-Q™ once started. Participants took a median of 23 minutes to complete the online process. Patient-reported clinical data were accurate in 12 of 13 domains compared with electronic records (95 per cent concordance). Process evaluation demonstrated acceptability. Conclusion: The results of this pilot demonstrate the online platform to be acceptable, feasible, and accurate for this population from a single institution. The low-burden design may enable participation from centres with less research support and participants from hard-to-reach groups or dispersed geographical locations, but with online access. Abstract : Participation in research in beneficial but can be challenging at a participant, clinician and organisation level. A novel online recruitment and data collection platform has been designed to improve accessibility to research and reduce the burden for participants and centres. The pilot study has demonstrated the platform to be feasible, acceptable to patients and accurate. Useful template when resources limited.